2016
DOI: 10.1038/nmat4727
|View full text |Cite
|
Sign up to set email alerts
|

Intrusion rheology in grains and other flowable materials

Abstract: The interaction of intruding objects with deformable materials is a common phenomenon, arising in impact and penetration problems, animal and vehicle locomotion, and various geo-space applications. The dynamics of arbitrary intruders can be simplified using Resistive Force Theory (RFT), an empirical framework originally used for fluids but works surprisingly well, better in fact, in granular materials. That such a simple model describes behavior in dry grains, a complex nonlinear material, has invigorated a se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 43 publications
1
65
0
1
Order By: Relevance
“…In the past decades, the interest has been broadened in connection with crater formation [8][9][10][11] , partly motivated by space exploration 12,13 as well as deciphering the history of planet formation 4 . Moreover, it has been extended to the influence of air cavity collapsing as well as granular jet formation 14 , the projectile shape 11,15,16 and the role of gravity on the final penetration depth and time 17 . As an extreme case, infinite penetration of a projectile into light-weighted EPS (expanded polystyrene) particles was observed, when the weight of the projectile exceeds a critical value 18 .…”
Section: Introductionmentioning
confidence: 99%
“…In the past decades, the interest has been broadened in connection with crater formation [8][9][10][11] , partly motivated by space exploration 12,13 as well as deciphering the history of planet formation 4 . Moreover, it has been extended to the influence of air cavity collapsing as well as granular jet formation 14 , the projectile shape 11,15,16 and the role of gravity on the final penetration depth and time 17 . As an extreme case, infinite penetration of a projectile into light-weighted EPS (expanded polystyrene) particles was observed, when the weight of the projectile exceeds a critical value 18 .…”
Section: Introductionmentioning
confidence: 99%
“…For vertical uplift loadings, the maximum drag F s is proportional to the vertical hydrostatic normal stress σ h at the object depth: reported values ranging from 1 to 100. Several studies have shown how this parameter varies with the internal friction angle φ of the packing [3,[7][8][9][10][11], the object shape [12][13][14][15][16] and the grain size [17][18][19]. The experimental method used to measure this parameter consists of uplifting the object at a constant and relatively slow velocity and monitoring the drag force during the uplift.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the dynamic response of granulate media during locomotion is difficult to predictively simulate or replicate [9,15,1]. In desert environments, this difficulty is compounded by the heterogeneous composition of the loose, sandy topsoil, making it nearly impossible to predict the effectiveness of any locomotor strategy a priori [9,1].…”
Section: Related Workmentioning
confidence: 99%
“…Unfortunately, the dynamic response of granulate media during locomotion is difficult to predictively simulate or replicate [9,15,1]. In desert environments, this difficulty is compounded by the heterogeneous composition of the loose, sandy topsoil, making it nearly impossible to predict the effectiveness of any locomotor strategy a priori [9,1]. In practice, the performance of robotic systems in heterogeneous granulate media, particularly in xeric habitats, must be evaluated post-hoc and iteratively improved (see for example [15]) through successive design refinements and adaptive learning of locomotion.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation